Bhutan: Can the 1.5 °C agenda be integrated with growth in wealth and happiness? - Yangka, D.; Newman, Peter (Cogitatio, 2018)
© 2018 by the authors. Bhutan is a tiny kingdom nested in the fragile ecosystem of the eastern Himalayan range, with urbanisation striding at a rapid rate. To the global community, Bhutan is known for its Gross National Happiness (GNH), which in many ways is an expression of the Sustainable Development concept. Bhutan is less known for its policy of being carbon neutral, which has been in place since the 15th session of the Conference of Parties meeting in 2009 and was reiterated in their Nationally Determined Contribution with the Paris Agreement. Bhutan achieves its carbon neutral status through its hydro power and forest cover. Like most emerging countries, Bhutan wants to increase its wealth and become a middle income country by 2020, as well as increase its GNH. This article looks at the planning options to integrate the three core national goals of GNH, economic growth (GDP) and greenhouse gas (GHG). We investigate whether Bhutan can contribute to the 1.5 °C agenda through its ‘zero carbon commitment’ as well as growing in GDP and improving GNH. Using the Long-range Energy Alternatives Planning model, this article shows that carbon neutral status would be broken by 2037 or 2044 under a high GDP economic outlook, as well as a business as usual scenario. National and urban policy interventions are thus required to maintain carbon neutral status. Key areas of transport and industry are examined under two alternative scenarios and these are feasible to integrate the three goals of GHG, GDP and GNH. Power can be kept carbon neutral relatively easily through modest increases in hydro. The biggest issue is to electrify the transport system and plans are being developed to electrify both freight and passenger transport.